Território pesqueiro da Camboa dos Frades (São Luís/MA): na rede de resistência diante dos megaprojetos - Santos, Tatiane Nogueira (2023)
This research work to discuss how the social agentes of the Community of Camboa dos Frades mobilize and claim in contrast to the megaproject inslalled in the territory, this understanding its resistance through territorial conflicts. It is noted tha with the implementation and extension – under construction - of the Port of Itaqui has caused losses for the community, related to social dynamics, environment and territorial, in what unfolding in the discussion of territorial conflicts that cross traditional communities in São Luís (MA), constituting here with a critical analysis of such issues. In the meantime, this dissertation also aims to build understanding about the social mobilizations that occur in rural territory, bringing methodological basis, by a vision of ethnography and fieldwork in loco, taking for information collection, semi-structured interviews. Obtaining as a result the understanding of the struggles and social claims of the community Camboa dos Frades, being this traditional and rural territory of artisanal fishermen. It also leads to an understanding of how the development model has been damaging the socio- environmental scope of the territory. It is important to emphasize that the pressure on the territory comes not only from private interests, but also from the Maranhão State government itself (Flávio Dino). Currently, the region of Itaqui-Bacanga, where the community Camboa dos Frades is located, is seen as a strategic area for large maritime shipping, which provides international exportation, therefore widely advertised as a place for progress-development from the implementation of megaprojects, which denotes a false local "development". In view of this, there is an understanding of a continuous exploitation of the area, which has been the target of commercial monopoly desires since the colonial period. This research shows that the mega- projects are installed without any concern for the surroundings, the fishing territories, and the centuries-old community. In this sense, this research will give visibility to the recognition of the "specific territory" and the reflections contained in the resistance relations of these social agents of the Camboa dos Frades community.